Vesicoureteral Reflux in Children with Accidental Diagnosis of Unilateral Small Size Kidney - Mohsen Mohammadi; Khadijeh Ebrahimi; Soraya Khafri; Maryam Nikpour; Hadi Sorkhi (Urology Research and Practice)
Objective: A majority of small size kidney in children were diagnosed after a urinary tract infection (UTI) and with high-grade vesicoureteral reflux (VUR). This study was conducted in children who were diagnosed accidentally and investigated for VUR and UTI.